Few-layer hexagonal boron nitride / 3D printable polyurethane composite for neutron radiation shielding applications. (1st March 2023) - Knott, Jonathan C.; Khakbaz, Hadis; Allen, Jackson; Wu, Liang; Mole, Richard A.; Baldwin, Christopher; Nelson, Andrew; Sokolova, Anna; Beirne, Stephen; Innis, Peter C.; Frost, Dillon G.; Cortie, David; et al.
Abstract: Functional polymer composites can confer a range of benefits in practical applications that go beyond the individual properties of the constituent materials. Here we investigate and characterize the neutron absorbing capability of few-layer hexagonal boron nitride ( h -BN) in composite with a 3D-printable thermoplastic polyurethane, and present experiment and simulation data to understand the processes and mechanisms in play. Shielding and protection from neutrons can be necessary in a range of terrestrial and space-based applications. The neutron absorption of composites with varying fractions of h -BN is strongly energy-dependent in the low-energy regime below 10 meV, and a composite containing 20 wt% h -BN shows a 70-fold reduction in the transmission relative to pure polyurethane at 0.5 meV neutron energies. This is attributed to the strong neutron capture cross-section of the naturally abundant boron-10 isotope, with energy-dependent measurements up to 100 meV confirming this point. Using inelastic neutron spectroscopy, we identify additional effects from the hydrogen in the polyurethane which both scatters diffusively and moderates neutrons inelastically via its phonon spectrum, enhancing the neutron absorption characteristics. Two models – based on analytic functions and Monte Carlo numerical techniques – are presented, and show excellent agreement with experiment results. The 3D-printability of the composite is demonstrated, and the opportunities and challenges for deploying these composites in neutron radiation protection applications are discussed. Graphical abstract: Image 1 Highlights: Hexagonal boron nitride/3D-printable polyurethane ( h -BN/PU) composites show great promise for neutron radiation shielding. h -BN/PU composites show up to a 70-fold reduction in neutron transmission compared to PU-only material. A portfolio of 'explanatory' and 'exploratory' models show the processes occurring across a range of neutron energies. These models can be used to design and optimize h -BN/PU composites for a range of shielding applications.